Black women - Glickman, Courtney Paige; Le, Huynh-Nhu; Robertson, Hillary; Arbit, Ruthie; Danielson, Aimee; Patchen, Loral; Fries, Melissa; Scott, Rachel; Biel, Matthew (Journal of Maternal and Child Health, 2020)
Background: Untreated perinatal depression is a significant public health issue that disproportionately affects low-income black women and may lead to higher maternal mortality rates and disparate birth outcomes. Despite the growing literature documenting prevalence and risk for perinatal depression among black women, our knowledge of patient preferences of mental health interventions in obstetrical (OB) settings among this population is limited. This study explored mental health treatment preferences among black pregnant and postpartum women in an urban OB practice, serving predominantly black women with public insurance. Subjects and Method: The study sample consisted of 14 perinatal women at an urban obstetrics practice in Washington, DC. Semi-structured interviews were conducted to gain insight into their emotional experiences during pregnancy and postpartum, and to obtain patient recommendations for mental health interventions within an obstetrics setting. Patient interviews were audio-recorded, transcribed, and analyzed by two coders using inductive thematic analysis and consensus procedures.